O que tem vida sobrevive : estudo para a conservação e restauro de obras em têmpera vinílica sobre platex : uma pintura de Pedro Cabrita Reis das coleções da FBAUL - Marques, Maria Dulce Marçal, 1964- (2017)
In the area of conservation and restoration of contemporary artwork, the introduction of new materials by artists has been requiring a new approach. This approach is developed by collecting information about procedures, useful for professionals in this area. Then comes the need to address both practical and theoretical knowledge of experts from different areas. During this study, in order to seek in-depth knowledge of some of these materials (hardboard and vinyl temper), approaches have been developed by and to professionals in the field of conservation and restoration, the artist Cabrita Reis, producers of hardboard in Portugal and whitch vinyl temper was used, all in order to gather knowledge of these material’s characteristics, know how they behave and what to do if certain changes occur, as well as the possibility of shrinkage of intervention, taking into account the respect for materials